Production Factor Performance and Allocative Efficiency Arabica Coffee Farming in Kayumas Village - Iqlima Liyusak Al Islami; Indriyani Indriyani; Mohammad Rizal Hidayat; Muhammad Barry Nur Anhar; Puryantoro Puryantoro (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Coffee is one of the plantation commodities that has an essential role in Indonesia's economic activities. Kayumas Village, Arjasa District, Situbondo Regency, is the area that grows the most Arabica coffee compared to other areas in Situbondo Regency. The decline in selling prices and demand for coffee is one of the existing problems, so it is necessary to use coffee production factors efficiently so that farmers can still get maximum profits. This research aims to identify factors that influence Arabica coffee production and the allocative efficiency of Arabica coffee farming. Secondary and primary data collected through interviews and observations were analyzed using the Cobb-Douglas method and the allocative efficiency formula. The number of respondents was 20 people in the Sejahtera farmer group in Kayumas Village, Arjasa District. Determining respondents used a saturated sampling technique because there were fewer sample farmers than 30 people. The results of this research show that the production factors are land area (X1), number of coffee trees (X2), labor (X3), organic fertilizer (X4), age of coffee plants (X5), distance from house to land (X6), and shade plants. (X7) simultaneously influences coffee production. However, partially, the production factors that influence coffee production include land area (X1 ), age of the coffee plant (X5), and distance from house to land (X6), with a significance of less than 0.05. The level of allocative efficiency of the production factors of land area and organic fertilizer is still not efficient, while the production factors of labor and the number of trees are not yet efficient, so to achieve this level of efficiency, the input in the form of labor and the number of trees must be reduced. This differs from the land area and organic fertilizer that farmers need to increase to reach an efficient level in Arabica coffee production.